'Lunchtimes in New Zealand are cruel': reflection as a tool for developing language learners' intercultural competence. Issue 4 (8th August 2018) - Conway, Clare; Richards, Heather
ABSTRACT: Reflection as a tool for the development of an intercultural dimension in language learning is mentioned to varying degrees in curriculum documents, guidelines and the literature. While there is a call for teachers to encourage language learners to engage in reflection for the development of intercultural competence (IC), studies show it can be challenging to implement in the classroom. This paper considers the extent to which language teachers in New Zealand schools provided opportunities for learners to develop aspects of IC through reflection. Findings from a nationwide survey and interviews with teachers of six foreign languages indicate that many teachers were limited in both their understanding and use of reflection as a learning tool. However, two examples are given of how teachers did provide opportunities that encouraged their learners to reflect on their own culture and on the culture of others. From examples, we summarise strategies that may assist in scaffolding learners into reflection, and call for focussed language teacher professional development.